Meloidae of Namibia (Coleoptera): taxonomy and faunistics with biogeographic and ecological notes - Bologna, Marco A.; Amore, Valentina; Pitzalis, Monica (Zootaxa, 2018)
The blister beetle (Coleoptera: Meloidae) fauna of Namibia is studied. The species are arranged within a catalogue containing information on their general distribution, including a list of localities and brief taxonomic remarks. Zoogeographic and ecological analyses were carried out and a photographic appendix, with images and maps of almost all Namibian species, is included. According to a chorological analysis, the Namibian blister beetle fauna appears to be zoogeographically distinct because of the dominance of western southern African elements. The faunistic levels of similarity among distinct areas in Namibia are also analysed. Several of the endemic species are related to the xeric ecosystems referable to the Namib Desert, Succulent Karoo and Nama Karoo biomes, but the highest diversity is related to the ecosystems referable to the Savannah biome. A total of 148 species belonging to 28 genera, eight tribes and three subfamilies (Eleticinae,  Meloinae, Nemognathinae) are recorded from this southern African country. Five new genera (Namibeletica gen. nov., Eleticinae Eleticini; Dilatilydus gen. nov. and Desertilydus gen. nov., Meloinae Lyttini; Paramimesthes gen. nov. and Namylabris gen. nov, Meloinae Mylabrini) and a total of 13 new species are described: 11 new species from Namibia (Psalydolytta gessi sp.nov., Paramimesthes namibicus sp.nov., Namylabris adamantifera sp.nov., Hycleus arlecchinus sp.nov., H. planitiei sp.nov., H. dvoraki sp.nov., H. aridus sp.nov., H. san sp.nov., Nemognatha fluviatilis sp.nov., “Zonitoschema” deserticola sp.nov., Zonitoschema dunalis sp.nov.); a new Namibeletica from the Angolan Namib (N. angolana) and a new Afrolytta Kaszab, 1959 from the S African Namaqualand (A. namaqua), both close to Namibian borders. Fourty-eight species and the genus Apalus Fabricius, 1775 are recorded for the first time from Namibia, and a few other species from South Africa (1), Zambia (1), Botswana (1) and Congo (1). The following new synonymies are proposed: Lytta pleuralis var. inpleuralis Pic, 1911 = Lydomorphus (Lydomorphus) thoracicus (Erichson, 1843), syn. nov.; Lytta benguellana Pic, 1911 = Prionotolytta melanura (Erichson, 1843), syn. nov.; Actenodia amoena ssp.anthicoides Kaszab, 1955b = Hycleus amoenus (Marseul, 1872), syn. nov.; Decapotoma csikii Kaszab, 1953 = Hycleus benguellanus (Marseul, 1879), syn. nov.; Nemognatha capensis Péringuey, 1909 = Nemognatha peringueyi Fairmaire, 1883, syn. nov. Several new combinations in the genus Hycleus Latreille, 1817 are also established.